1941 жылғы 316-атқыштар дивизиясындағы саяси қызметкерлер (Журналистика сериясы, 2020)
Based on the materials of the Central Archive of the Ministry of Defense of the Russian Federation and the Central State Archive of the Republic of Kazakhstan, published and unpublished memoirs of surviving veterans of the division, materials of Internet bases search, lists of political workers of the 316th rifle division in 1941 were collected and prepared. In the article, as a result of studying the lists, a col- lective portrait of the political workers of the division was given, the average age of the political workers was calculated, their fates were shown, the author’s answer to the question why they became the most famous division, causing the most fierce disputes in the modern period was given. Educational, political, propaganda work in the 316th rifle division was different from other military units of 1941, the times of retreats and defeats. How did they survive? Why, retreating, they won? All these difficult issues should be studied not only in military schools, but also in schools, colleges, universities.Purpose: studying recently discovered materials of the Central archive of the Ministry of Defence of the Russian Federation and Central State archive of the Republic of Kazakhstan on the 316th rifle division of I.V. Panfilov in 1941.The practical significance of the study is the use of its results in the field of culture, history, traditions, education, training, survival skills in the most difficult conditions, life skills. Knowledge of history, philoso- phy of victory, psychology in times of crisis is necessary for political scientists, journalists, experts, psychol- ogists, the military, educators and teachers, students, undergraduates and doctoral students of universities. The results of the study can be integrated into educational, ideological, pedagogical and educational processes. The experience of Kazakhstan can be presented as a practice for the new history of the post-Soviet countries and in the republic itself. Materials can be included in textbooks of the history of the twentieth century, journalism, psychology and other socio-humanitarian disciplines.
Keywords: И.В. Панфилов атындағы 316-атқыштар дивизиясы, саяси қызметкерлер, Ресей қорғаныс министрлігінің орталық архивтері, ҚР орталық мемлекеттік мұрағаттары, іздеу жүйелері.